Synthesis and characterization of benzodithiophene and benzotriazole-based polymers for photovoltaic applications - Gedefaw, Desta; Tessarolo, Marta; Bolognesi, Margherita; Prosa, Mario; Kroon, Renee; Zhuang, Wenliu; Henriksson, Patrik; Bini, Kim; Wang, Ergang; Muccini, Michele; Seri, Mirko; Andersson, Mats R. (Beilstein Journal of Organic Chemistry, 2016)
Two high bandgap benzodithiophene–benzotriazole-based polymers were synthesized via palladium-catalysed Stille coupling reaction. In order to compare the effect of the side chains on the opto-electronic and photovoltaic properties of the resulting polymers, the benzodithiophene monomers were substituted with either octylthienyl (PTzBDT-1) or dihexylthienyl (PTzBDT-2) as side groups, while the benzotriazole unit was maintained unaltered. The optical characterization, both in solution and thin-film, indicated that PTzBDT-1 has a red-shifted optical absorption compared to PTzBDT-2, likely due to a more planar conformation of the polymer backbone promoted by the lower content of alkyl side chains. The different aggregation in the solid state also affects the energetic properties of the polymers, resulting in a lower highest occupied molecular orbital (HOMO) for PTzBDT-1 with respect to PTzBDT-2. However, an unexpected behaviour is observed when the two polymers are used as a donor material, in combination with PC61BM as acceptor, in bulk heterojunction solar cells. Even though PTzBDT-1 showed favourable optical and electrochemical properties, the devices based on this polymer present a power conversion efficiency of 3.3%, considerably lower than the efficiency of 4.7% obtained for the analogous solar cells based on PTzBDT-2. The lower performance is presumably attributed to the limited solubility of the PTzBDT-1 in organic solvents resulting in enhanced aggregation and poor intermixing with the acceptor material in the active layer.
Keywords: alkyl side chains; benzodithiophene; bulk heterojunction solar cells; 2D conjugated polymers; fluorinated benzotriazole

(untitled) - Kroon, R.; Diaz de Zerio Mendaza, A.; Himmelberger, S.; Bergqvist, J.; Bäcke, O.; Faria, G. C.; Gao, F.; Obaid, A.; Zhuang, W.; Gedefaw, D.; Olsson, E.; Inganäs, O.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Boudreault, P.-L. T.; Najari, A.; Leclerc, M. (Chem. Mater., 2011)

(untitled) - Lv, M.; Lei, M.; Zhu, J.; Hirai, T.; Chen, X. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Matsidik, R.; Komber, H.; Luzio, A.; Caironi, M.; Sommer, M. (J. Am. Chem. Soc., 2015)

(untitled) - Li, X.; Choy, W. C. H.; Huo, L.; Xie, F.; Sha, W. E. I.; Ding, B.; Guo, X.; Li, Y.; Hou, J.; You, J.; Yang, Y. (Adv. Mater., 2012)

(untitled) - He, Z.; Zhong, C.; Su, S.; Xu, M.; Wu, H.; Cao, Y. (Nat. Photonics, 2012)

(untitled) - Dou, L.; You, J.; Yang, J.; Chen, C.-C.; He, Y.; Murase, S.; Moriarty, T.; Emery, K.; Li, G.; Yang, Y. (Nat. Photonics, 2012)

(untitled) - You, J.; Dou, L.; Yoshimura, K.; Kato, T.; Ohya, K.; Moriarty, T.; Emery, K.; Chen, C.-C.; Gao, J.; Li, G.; Yang, Y. (Nat. Commun., 2013)

(untitled) - Espinosa, N.; Hösel, M.; Jørgensen, M.; Krebs, F. C. (Energy Environ. Sci., 2014)

(untitled) - Emmott, C. J. M.; Röhr, J. A.; Campoy-Quiles, M.; Kirchartz, T.; Urbina, A.; Ekins-Daukes, N. J.; Nelson, J. (Energy Environ. Sci., 2015)

(untitled) - Berny, S.; Blouin, N.; Distler, A.; Egelhaaf, H.-J.; Krompiec, M.; Lohr, A.; Lozman, O. R.; Morse, G. E.; Nanson, L.; Pron, A.; Sauermann, T.; Seidler, N.; et al. (Adv. Sci., 2016)

(untitled) - Roth, B.; dos Reis Benatto, G. A.; Corazza, M.; Carlé, J. E.; Helgesen, M.; Gevorgyan, S. A.; Jørgensen, M.; Søndergaard, R. R.; Krebs, F. C. (Adv. Eng. Mater., 2016)

(untitled) - Li, Y. (Acc. Chem. Res., 2012)

(untitled) - Kim, J.-H.; Song, C. E.; Shin, N.; Kang, H.; Wood, S.; Kang, I.-N.; Kim, B. J.; Kim, B.; Kim, J.-S.; Shin, W. S.; Hwang, D.-H. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Price, S. C.; Stuart, A. C.; Yang, L.; Zhou, H.; You, W. (J. Am. Chem. Soc., 2011)

(untitled) - Kim, J.-H.; Kim, H. U.; Song, C. E.; Kang, I.-N.; Lee, J.-K.; Shin, W. S.; Hwang, D.-H. (Sol. Energy Mater. Sol. Cells, 2013)

(untitled) - Bolognesi, M.; Gedefaw, D.; Dang, D.; Henriksson, P.; Zhuang, W.; Tessarolo, M.; Wang, E.; Muccini, M.; Seri, M.; Andersson, M. R. (RSC Adv., 2013)

(untitled) - Gedefaw, D.; Tessarolo, M.; Zhuang, W.; Kroon, R.; Wang, E.; Bolognesi, M.; Seri, M.; Muccini, M.; Andersson, M. R. (Polym. Chem., 2014)

(untitled) - Unay, H.; Unlu, N. A.; Hizalan, G.; Hacioglu, S. O.; Yildiz, D. E.; Toppare, L.; Cirpan, A. (J. Polym. Sci., Part A: Polym. Chem., 2015)

(untitled) - Wong, W. W. H.; Subbiah, J.; Puniredd, S. R.; Pisula, W.; Jones, D. J.; Holmes, A. B. (Polym. Chem., 2014)

(untitled) - Tessarolo, M.; Gedefaw, D.; Bolognesi, M.; Liscio, F.; Henriksson, P.; Zhuang, W.; Milita, S.; Muccini, M.; Wang, E.; Seri, M.; Andersson, M. R. (J. Mater. Chem. A, 2014)

(untitled) - Tregnago, G.; Steckler, T. T.; Fenwick, O.; Andersson, M. R.; Cacialli, F. (J. Mater. Chem. C, 2015)

(untitled) - Li, Z.; Lin, H.; Jiang, K.; Carpenter, J.; Li, Y.; Liu, Y.; Hu, H.; Zhao, J.; Ma, W.; Ade, H.; Yan, H. (Nano Energy, 2015)

(untitled) - Yuan, M.-C.; Chiu, M.-Y.; Chiang, C.-M.; Wei, K.-H. (Macromolecules, 2010)

(untitled) - Wang, B.; Zhang, J.; Tam, H. L.; Wu, B.; Zhang, W.; Chan, M. S.; Pan, F.; Yu, G.; Zhu, F.; Wong, M. S. (Polym. Chem., 2014)

(untitled) - Osaka, I.; Saito, M.; Koganezawa, T.; Takimiya, K. (Adv. Mater., 2014)

(untitled) - Hellström, S.; Zhang, F.; Inganäs, O.; Andersson, M. R. (Dalton Trans., 2009)

(untitled) - Brabec, C. J.; Cravino, A.; Meissner, D.; Sariciftci, N. S.; Fromherz, T.; Rispens, M. T.; Sanchez, L.; Hummelen, J. C. (Adv. Funct. Mater., 2001)

(untitled) - Huo, L.; Hou, J.; Zhang, S.; Chen, H.-Y.; Yang, Y. (Angew. Chem., Int. Ed., 2010)

(untitled) - Bredas, J.-L. (Mater. Horiz., 2014)

(untitled) - Chen, Z.-K.; Huang, W.; Wang, L.-H.; Kang, E.-T.; Chen, B. J.; Lee, C. S.; Lee, S. T. (Macromolecules, 2000)